Literature Review: Directions of Economic Development and Green Finance in Indonesia - Triandarto, Farid (International Conference On Economics Business Management And Accounting (ICOEMA), 2024)
Generally, a green economy will change the established economic system to be more in line with sustainable principles. This is the main challenge in realising a green economy. The purpose of this research is to provide information and understanding of the direction of green economy development in Indonesia and the importance of combining economic and environmental elements in sustainable development, as well as to thoroughly analyse the challenges and prospects of a sustainable green economy in Indonesia. The research uses descriptive qualitative research methods with literature review techniques. The analysis stages used are three, namely analysing the contents of the journal, coding the contents of the journal using bibliometric analysis, then looking for similarities and differences and then discussing them to draw conclusions. The study concludes that green economic development in Indonesia aims to achieve sustainable and inclusive economic growth, taking into account environmental and social aspects. Some of the main directions in this development include increasing the use of renewable energy, sustainable natural resource management, waste management and recycling, environmentally friendly transport, green city development, green industry, circular economy, sustainable water management, and strengthening policies and regulations.